Clonotypic architecture of a Gag‐specific CD8+ T‐cell response in chronic human HIV‐2 infection. Issue 10 (7th September 2021) - Moysi, Eirini; Darko, Samuel; Gea‐Mallorquí, Ester; Petrovas, Constantinos; Almeida, Jorge R.; Wolinsky, David; Peng, Yanchun; Jaye, Assan; Stewart‐Jones, Guillaume; Douek, Daniel C.; Koup, Richard A.; Dong, Tao; et al.
Abstract: The dynamics of T‐cell receptor (TCR)selection in chronic HIV‐1 infection, and its association with clinical outcome, is well documented for an array of MHC‐peptide complexes and disease stages. However, the factors that may contribute to the selection and expansion of CD8+ T‐cells in chronic HIV‐2 infection, especially at the clonal level remain unclear. To address this question, we undertook a detailed molecular characterization of the clonotypic architecture of an HLA‐B*3501 restricted Gag‐specific CD8+ T‐cell response in donors chronically infected with HIV‐2 using a combination of flow cytometry, tetramer‐specific CD8+ TCR clonotyping, and in vitro assays. We show that the response to the NY9 epitope is hierarchical and narrow in terms of T‐cell receptor‐alpha (TCRA) and ‐beta (TCRB) gene usage yet clonotypically diverse. Furthermore, clonotypic dominance in shared origin CTL clones was associated with a greater magnitude of cytokine production and antigen sensitivity at limiting antigen dilution as well as enhanced cross‐reactivity for known HIV‐2 variants. Hence, our data suggest that effector mobilization and expansion in human chronic HIV‐2 infection may be linked to the qualitative features of specific CD8+ T‐cell clonotypes, which could have implications for viral control and disease outcome. Abstract : Through an integrated analysis of T‐cell receptor repertoire usage in chronic human HIV‐2 infection, we determine parameters associated with the recruitment and expansion of Gag‐specific CTL. These results shed light into CD8+ T‐cell selection dynamics and mechanisms that could potentially contribute to viral control.